Organizacija organa uprave na osnovu zakona u institucijama Bosne i Hercegovine i Federacije Bosne i Hercegovine / The Administrative Bodies Organization in the BH Institutions and Federation of Bosnia and Herzegovina - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
The existing Law on Administration, Law on Organizing Administration in the FBiH, Law on Ministries and other BH Government Authorities, Law on Federal Ministries and other Federal Administrative Bodies, Law on Ministerial Appointments, Council of Ministers Appointments and other FBiH Appointments, Law on Ministerial, Government Appointments and other appointments in FBiH, Law on civil service in the BH institutions, Law on Civil Service in the FBiH, Law on Employees in the FBiH Civil Service and the Law on Inspections in the FBiH contain provisions on the various administrative organizations, their mutual relations and managers, civil service law, inspection and funds for the administration work. Legally, the existence of these laws in the administrative and legal order is not necessary. The author in the paper proposes the merging of these laws into the new Laws on Council of Ministers Administration Organizing, Organization of Administration Bodies in the FBiH and the adoption of the Law on Inspection Control in FBiH as a special administrative procedure. The general part of the Federal law would comprise norms common to all government levels in the Federation of Bosnia and Herzegovina, as special part of the provision would be reserved only for the federal level of government authority. In a separate part provisions on the jurisdiction of the Ministries of Finance, Justice, and Labor and Social Policy should be supplemented. Such reform would not violate the applicable rules in the Law on Administration and the Law on Organizing Administration in the FBiH; providing that the law establishes administrative bodies and institutions with public authority. The current administrative laws in BiH wrongly treat the theoretical concept of the administrative organization. This paper demands the introduction of the generic term - administration authority instead.